Study on the mechanism of Huangqi Guizhi Wuwu Decoction in treating diabetes peripheral neuropathy based on network pharmacology and molecular docking: Huangqi Guizhi Wuwu Decoction for diabetic neuropathy - Ai, Bichen; Zhang, Weihua; Li, Guojing (Cellular and Molecular Biology, 2024)
This study aimed to explore the effective substances and mechanism network of Huangqi Guizhi Wuwu Decoction in treating diabetes peripheral neuropathy. Based on the TCM systemic pharmacological analysis platform (TCMP) and UniProt database, the database of active Huqarqu Decoction was constructed, and the related targets of diabetic peripheral neuropathy were collected through the OMIM, CTD, DisGeNET, TTD and GeneCards databases. The intersection targets were obtained to construct the network diagram of Huangqi dis Guizhi Wuwu Decoction-Active Through the String database, the interaction between target proteins was analyzed, and molecular docking between active components and potential targets was carried out. Combined with the DAVID v6.8 database, GO function analysis and KEGG pathway analysis were performed on the targets. Guizhi Wuwu Decoction mainly acts on core targets such as IL6, MAPK3, VE GFA, JUN and ESR1 through quercetin, kaempferol and naringin and regulates the TNF signaling pathway, estrogen signaling pathway and MAPK signaling pathway, thus achieving the effect of treating diabetes peripheral neuropathy. Huangqi Guizhi Wu has multiple targets and regulates multiple signaling pathways in neuropathy, which lays a foundation for future pharmacological research.